The acetyltransferase enzyme method for the assay of serum gentamicon concentrations and a comparison with other methods. Issue 2 (February 1975) - Broughall, J M; Reeves, D S
Abstract : The adenylytransferase/acetyltransferase methods of gentamicin assay have been evaluated for accuracy, speed, and cost. For a comparable cost of materials the latter method is more accurate than that using the adenylytransferase enzyme. The acetyltransferase method is much quicker than the adenyltransferase due to the shorter time necessary for radioactive counting. Sonication is an easier method of enzyme preparation than the previously used osmotic shock technique. The acetyltransferase method is reproducible and there was a very good correlation between it and a microbiological agar-plate diffusion method.